2017
DOI: 10.1002/ijc.30832
|View full text |Cite
|
Sign up to set email alerts
|

Spatial clustering of childhood leukaemia in Switzerland: A nationwide study

Abstract: The aetiology of childhood leukaemia remains largely unknown. Several hypotheses involve environmental exposures that could implicate spatial clustering of cases. The evidence from previous clustering studies is inconclusive. Most of them used areal data and thus had limited spatial resolution. We investigated whether childhood leukaemia tends to cluster in space using exact geocodes of place of residence both at the time of birth or diagnosis. We included 1,871 leukaemia cases diagnosed between 1985 and 2015 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 48 publications
3
14
0
Order By: Relevance
“…The general picture shows mixed results for childhood leukaemia and weak or no evidence of spatial clustering of lymphoma and CNS tumours [35][36][37]. In previous studies using the same data, we found no evidence of clustering of childhood cancers, leukaemia, lymphoma or CNS tumours, but weak evidence, consistent with the literature, for Hodgkin lymphoma and embryonal CNS tumours [38,39]. We observed a cluster of intracranial and intraspinal CNS tumours in the French speaking part of Switzerland consistent with the pattern observed for CNS tumours in the present study [38].…”
Section: Comparison Of Our Study With Other Spatial Analyses Of Childsupporting
confidence: 76%
“…The general picture shows mixed results for childhood leukaemia and weak or no evidence of spatial clustering of lymphoma and CNS tumours [35][36][37]. In previous studies using the same data, we found no evidence of clustering of childhood cancers, leukaemia, lymphoma or CNS tumours, but weak evidence, consistent with the literature, for Hodgkin lymphoma and embryonal CNS tumours [38,39]. We observed a cluster of intracranial and intraspinal CNS tumours in the French speaking part of Switzerland consistent with the pattern observed for CNS tumours in the present study [38].…”
Section: Comparison Of Our Study With Other Spatial Analyses Of Childsupporting
confidence: 76%
“…The general picture shows mixed results for childhood leukaemia and weak or no evidence of spatial clustering of lymphoma and CNS tumours [33][34][35]. In previous studies using the same data, we found no evidence of clustering of childhood cancers, leukaemia, lymphoma or CNS tumours, but weak evidence, consistent with the literature, for Hodgkin lymphoma and embryonal CNS tumours [36,37]. We observed a cluster of intracranial and intraspinal CNS tumours in the French speaking part of Switzerland consistent with the pattern observed for CNS tumours in the present study [36].…”
Section: Comparison Of Our Study With Other Spatial Analyses Of Childsupporting
confidence: 76%
“…Most of these clusters were discovered incidentally and it is not possible, in retrospect, to judge whether they represent true deviations from a flat risk scenario. Indeed in a recent systematic investigation of spatial clustering in Switzerland, we found that quite remarkable aggregations of cases are well compatible with a flat risk scenario (Konstantinoudis et al, 2017). Disease mapping is another approach of identifying areas of high risk, that may be more sensitive to areas of irregular shapes and long range spatial trends.…”
Section: Childhood Leukaemia Incidence In the Canton Of Zürichmentioning
confidence: 56%